2021
DOI: 10.3390/jpm11040297
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus australis and Ralstonia pickettii as Major Microbiota in Mesotheliomas

Abstract: The microbiota has been reported to be correlated with carcinogenesis and cancer progression. However, its involvement in the pathology of mesothelioma remains unknown. In this study, we aimed to identify mesothelioma-specific microbiota using resected or biopsied mesothelioma samples. Eight mesothelioma tissue samples were analyzed via polymerase chain reaction (PCR) amplification and 16S rRNA gene sequencing. The operational taxonomic units (OTUs) of the effective tags were analyzed in order to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…However this study did not involve with the microbiome of BALF, as well as the relationship of microbiome between BALF and tumor tissues. In our study, we found reduced genera including Ralstonia , Lactobacillus , unidentified-Chloroplast , and Pseudomonas in the GGO group, Among them, Ralstonia pickettii was found to be a mesothelioma specific microbiota involved in tumor progression ( Higuchi et al, 2021 ), and Lactobacillus induce anticancer effect by promoting cancer cell apoptosis and preventing oxidative stress, which is common in probiotics ( Badgeley et al, 2021 ), the effect on GGO can mechanically be interpreted by carcinogenesis due to the decreased genera. Interestingly, the most dominant phylum Proteobacteria is also significantly reduced.…”
Section: Discussionmentioning
confidence: 63%
“…However this study did not involve with the microbiome of BALF, as well as the relationship of microbiome between BALF and tumor tissues. In our study, we found reduced genera including Ralstonia , Lactobacillus , unidentified-Chloroplast , and Pseudomonas in the GGO group, Among them, Ralstonia pickettii was found to be a mesothelioma specific microbiota involved in tumor progression ( Higuchi et al, 2021 ), and Lactobacillus induce anticancer effect by promoting cancer cell apoptosis and preventing oxidative stress, which is common in probiotics ( Badgeley et al, 2021 ), the effect on GGO can mechanically be interpreted by carcinogenesis due to the decreased genera. Interestingly, the most dominant phylum Proteobacteria is also significantly reduced.…”
Section: Discussionmentioning
confidence: 63%
“…However, the involvement of this bacterium in the carcinogenesis of any organ has not been thoroughly studied. In the study by Higuchi et al [ 55 ], Streptococcus australis and R. pickettii were identified in almost all mesothelioma patients, but it is unclear whether the bacterial profiles with high levels of bacterial composition and abundance are causally associated with oncogenesis. Future studies with larger sample sizes are needed to determine their potential association with tumorigenesis and to explore the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma from the blood and the supernatant of the BAL fluid was centrifuged at 20,000× g for 10 min and the resultant supernatant was subsequently transferred to sterile tubes and stored at −80 °C before DNA extraction . To obtain DNA from tumors, the formalin-fixed, paraffin-embedded (FFPE) tissue sections were first stained with hematoxylin and eosin, and the tumor lesions were microdissected using the ArcturusXT laser-capture microdissection system for the following DNA extraction as also previously described [ 7 , 10 , 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%